MENGUAK FENOMENA SOCIAL LOAFING DI KALANGAN MAHASISWA YANG PATAH HATI - Andra Ryos Pradipta; Edy Raharja (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to analyze a phenomenon called social loafing that occurs in students, especially those who are or have experienced heartbreak. Based on social loafing which is a tendency for individuals to expend less effort (Myers, 2012)it often occurs in employees of an organization or company. However, it is possible for students as future HR candidates who often carry out group responsibilities because of a factor, one of which is heartbreak. This research was conducted qualitatively using the phenomenological method, which means interviewing students as resource persons who have experienced social loafing when they have group responsibilities both in organizations and study groups where the results contain the phenomenon itself, itsimpact, and the best solution for the resource person which is compiled so that be a research answer. The results showed that it was true that there was a social loafing phenomenon that occurred in heartbroken students. This phenomenon affects the performance in the group and affects the situation in the group and as a result theresults of the group are not optimal. Solutions in dealing with social loafing certainly vary, including group evaluation, self-introspection, and healing. Referring to the previous literature that examines the workforce, it shows the significance of the occurrence of social laziness on student/individual performance affecting group performance.